Implementasi Problem Based Learning (PBL) Dalam Pembelajaran Al-Qur’an Hadits - Munzaroh, Hanin; Khusni Albar, Mawi (Ngaos: Jurnal Pendidikan dan Pembelajaran, 2025)
This study aims to analyse the implementation of the Problem-Based Learning (PBL) model in Al-Qur'an Hadith learning at MTs Darwata Majenang, which is motivated by low student participation and limited understanding of the material due to the dominance of conventional teacher-centred methods. PBL was chosen because it uses real-world problems as the starting point for learning, thereby encouraging students to think critically, collaborate, and connect the material to real-life contexts. This study employs a qualitative approach using observation, in-depth interviews, and documentation techniques, analysed interactively through data reduction, presentation, and conclusion-drawing stages. The results of the study indicate that PBL is implemented through structured planning, organisation, implementation, and evaluation, with the integration of relevant social phenomena into the material. This implementation increases student engagement, analytical skills, presentation skills, courage to express opinions, and internalisation of Islamic values. PBL also strengthens cooperation, effective communication, and a participatory classroom atmosphere. Theoretically, this study enriches the literature on the application of PBL based on Islamic values in madrasahs. Practically, the results provide guidance for teachers in designing active learning that comprehensively integrates cognitive, affective, and psychomotor aspects, making Qur'an Hadith learning more contextual, meaningful, and relevant to the character development of students.